Incidence of hiatus hernia among semi-urban population with upper gastrointestinal symptoms: a single cantered study - E., Arvind; R., Murugan; M. P., Karthick; P., Karthick; G., Vikraman (International Surgery Journal, 2022)
Background: Hiatal hernias are a common occurrence in the western population, with an estimated prevalence of 15% to 20%. These hernias may become symptomatic and lead to gastroesophageal reflux disease (GERD), dysphagia, dyspnoea, and may affect cardiac and respiratory function. Being overweight and elderly are the key risk factors in its development.Other known risk factors include: multiple pregnancies, history of oesophageal surgery, partial or full gastrectomy and certain disorders of the skeletal system associated with bone decalcification and degeneration. Methods: This is a retrospective study done on patients who presented to the surgical outpatient at Trichy SRM Medical College Hospital and Research Centre during the period July 2021 to July 2022. Results: Total of 97 (19.02%) patients presented with lax hiatus 41 (42.27%) and had it exclusively while 5 (5.16%), 31 (31.96%), 10 (10.31%) and 10 (10.31%) had it associated with antral gastritis, diffuse gastritis, pan gastritis and oesophagitis respectively. These values were statistically significant with a p value <0.001. And lax hiatus was more commonly seen among female 56 (57.73%) compared to male 41 (42.27%) and hiatus hernia observed more in male 21 (58.33%) than female 15 (41.67%), there was no statistical significance observed among both the gender. Conclusions: Among the patients those who have presented to the surgery outpatient at Trichy SRM with upper gastrointestinal symptoms and in whom upper GI endoscopy were done the incidence of hiatus hernia was observed to be more prevalent among men compared to women in whom lax hiatus were seen to exist.